An Examination of Baron De Montesquieu's Separation of Power and Its Implications for Contemporary Nigerian Democracy - AKPAN, Victor Edem; DENNIS, Otto; IGNATIUS, Itohowo Paul (dialektika kontemporer, 2025)
The abuse of power remains a recurrent challenge in many democracies, especially where institutional checks are weak or ignored. Power, when left unchecked, often becomes a threat to the very people it is meant to serve. Against this backdrop, Baron de Montesquieu proposed the theory of separation of powers as a safeguard against tyranny, arguing that liberty thrives where the executive, legislature, and judiciary operate independently. This paper investigates how Montesquieu’s theory of power applies to the Nigerian democratic experience. The study aims to understand whether the division of power among Nigeria’s three arms of government is a facade or reality. Using a qualitative research methodology, the study deploys analytical, critical and expository methods in its data interpretation. Findings reveal that although the Nigerian Constitution stipulates separation of powers in theory, the principle is often compromised in practice. Frequent overlap and interference among the branches of government such as executive dominance, legislative inefficiency, and compromised judiciary have continued to challenge the ideal of balanced governance. This study argues that while Montesquieu’s theory remains relevant, its success depends on the willingness of leaders and institutions to respect the boundaries of power. Strengthening democratic practice in Nigeria requires more than borrowing ideals; it demands a commitment to fairness, transparency, and genuine institutional independence. The paper recommends a stronger enforcement of institutional independence, and political reforms that empower oversight functions. These steps are necessary if Nigeria is to build a democracy where power serves the people, not the interests of a few.